2018
DOI: 10.1155/2018/6310482
|View full text |Cite
|
Sign up to set email alerts
|

Research on Shape Feature Recognition of B-Rep Model Based on Wavelet Transform

Abstract: B-Rep (Boundary Representation) CAD model is widely used in the representation of manufactured product in computer, and it is a kind of real 3D structure with invisible part relative to 2.5D mesh model, so the shape feature recognition of B-Rep model is worth of much studying. We present one approach of shape feature recognition of B-Rep model based on the wavelet transform of surface boundary and region; it is inspired by the neuropsychology view that surface is the key visual features and by the systematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The former uses Deep 3D Convolutional Neural Networks (3D-CNNs) termed FeatureNet to learn machining feature from CAD models of mechanical parts, and the latter adopts Multiple Sectional View (MSV) representation for feature recognition. Gao et al [28] and Wang [29] employed optimization algorithm, such as ant colony searching algorithm and wavelet transform of surface boundary, to search the optimal face matching sequence between the two models. Kim et al [30] and Bespalov et al [31] suggested volume decomposition methods for feature recognition.…”
Section: Other Feature Recognition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former uses Deep 3D Convolutional Neural Networks (3D-CNNs) termed FeatureNet to learn machining feature from CAD models of mechanical parts, and the latter adopts Multiple Sectional View (MSV) representation for feature recognition. Gao et al [28] and Wang [29] employed optimization algorithm, such as ant colony searching algorithm and wavelet transform of surface boundary, to search the optimal face matching sequence between the two models. Kim et al [30] and Bespalov et al [31] suggested volume decomposition methods for feature recognition.…”
Section: Other Feature Recognition Methodsmentioning
confidence: 99%
“…According to the definition of bipartite graph in Formula (29), as well as the preceding definition of edge weights on model faces, a weighted complete bipartite graph is established, as shown in Fig. 4.…”
Section: A Construction Of Weighted Complete Bipartite Graphmentioning
confidence: 99%
“…All the same, the generation of the part geometry's STEP knowledge base plays an important role in understanding the dimensionality of the part. Primarily, the manufacturing machines consider the part's dimensions to a given machine's workspace [10]. This requires the part dimensions of the each-sided feature.…”
Section: Review Of Literature Surveymentioning
confidence: 99%